The Relationship between Quality Antenatal Care (ANC) Services and Pregnant Women's Satisfaction - Neti Kusumawati; Meti Megawati; Debby Syahru Romadlon; Bayu Irianti (Media Informasi, 2025)
Background: Optimal antenatal care (ANC) services play an important role in increasing the satisfaction of pregnant women during pregnancy visits to health workers. ANC visits need to be done routinely because it is important to monitor the health of the mother and fetus. Objective: This study aims to determine the level of satisfaction of pregnant women with ANC services at the Mangkubumi Health Center. Method: The study used a descriptive design with a cross-sectional approach. The study population was all pregnant women at the Mangkubumi Health Center, totaling 896 people. The sampling technique used was a purposive sampling technique with a solving formula; the total sample was 48 people. Data collection was done by filling out a service satisfaction questionnaire that included tangibles, reliability, responsiveness, assurance, and empathy. Data processing by editing, scoring, coding, tabulating, and analyzing descriptively. Results: The results showed that out of 48 respondents, 41 people (85.4%) were satisfied with ANC services, while pregnant women had a lower level of satisfaction, with 7 people (14.6%) being dissatisfied. The results of the chi-square statistical test obtained a P-value of 0.001 <0.005, with an odds-ratio value of 5.646. Conclusion: Based on the study's results, it can be concluded that quality ANC services have a significant relationship with the satisfaction of pregnant women. Suggestion: It is hoped that health workers will continue to maintain existing service aspects and increase responsiveness so that pregnant women are increasingly satisfied with ANC services.